Análisis de la narrativa visual de las fotografías con carácter político de la Revista Vistazo, período mayo-julio 2021 - Torres Aguilar, Wilson Andrés (2022)
The present investigative work establishes an analysis of the visual narrative of the photographs with a political nature in Vistazo Magazine, which occupy a significant space in each installment. As Ecuador goes through a hard-fought election season, political photographs become the first point of contact with citizens. These may suggest one message or another depending on their characteristics. In response to the needs of the present work, qualitative research methods and observation techniques were used, which allowed us to configure the knowledge of the visual narrative of the photographs with a political character, as well as marked differences between a photograph oriented to the cover of the magazine and those that graph the journalistic works within the magazine. It was possible to establish that the photographs with a political nature in the Vistazo Magazine follow patterns such as the low angle to suggest heroism, political subjects close to the citizenry or sitting with their legs crossed and a book in their hands. Likewise, the selection of images is strongly influenced by the media's editorial line and, on some occasions, political subjects are not treated with the same rigor